2012
DOI: 10.1364/ol.37.003411
|View full text |Cite
|
Sign up to set email alerts
|

Coherent transfer of optical orbital angular momentum in multi-order Raman sideband generation

Abstract: Experimental results from the generation of Raman sidebands using optical vortices are presented. By generating two sets of sidebands originating from different locations in a Raman active crystal, one set containing optical orbital angular momentum and the other serving as a reference, a Young's double slit experiment was simultaneously realized for each sideband. The interference between the two sets of sidebands was used to determine the helicity and topological charge in each order. Topological charges in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…This therefore limited the scope of the previous experiments. In the present work, we extend upon our earlier work [15] by investigating the production of Raman sidebands with higher-order helical beams such as the Laguerre Gaussian (LG) and Ince Gaussian (IG) modes; the non-helical even Laguerre Gaussian ( LG e ) and odd Laguerre Gaussian ( LG o ), and Hermite Gaussian modes (HG). From our experiments, we verify that the OAM-algebra holds for the high order helical-LG beams as well as for the helical-IG modes.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This therefore limited the scope of the previous experiments. In the present work, we extend upon our earlier work [15] by investigating the production of Raman sidebands with higher-order helical beams such as the Laguerre Gaussian (LG) and Ince Gaussian (IG) modes; the non-helical even Laguerre Gaussian ( LG e ) and odd Laguerre Gaussian ( LG o ), and Hermite Gaussian modes (HG). From our experiments, we verify that the OAM-algebra holds for the high order helical-LG beams as well as for the helical-IG modes.…”
Section: Introductionmentioning
confidence: 91%
“…Recently a number of investigations involving the nonlinear interaction of optical vortices with matter appeared in the literature [15][16][17]. In experiments presented in [15], the authors crossed time-delayed chirped pulses in a lead tungsten PbWO 4 crystal and demonstrated for the first time the coherent transfer of optical angular momentum in the generation of cascaded Raman sidebands. In these experiments, topological charge measurements verified a predicted orbital angular momentum algebra (OAM-algebra).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing utilization of femtosecond laser pulses renewed interest in self-focusing phenomena [19], development of beam instabilities [20] and small-scale self-focusing [21]], related to filamentation [22][23][24][25][26], white-light generation [22,[27][28][29][30][31][32][33] and conical emission [34]. White-light generation is usually accounted for by self-phase modulation [17,35], however stimulated Raman scattering [36,37], parametric four-wave mixing [38][39][40][41], and cascading of these effects as the beam propagates can also contribute to the generation of a supercontinuum. The question we are interested in is how the interaction of two crossing beams affects the white-light generation process.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated the mutual coherence of the spectral sidebands generated through molecular modulation in diamond and shown the capability to control spectral phases in a precise and stable manner in a setup that combined manual course adjustment of individual sideband phases with programmable pulse shaping and fine phase (and amplitude) tuning across the full spectrum [17,18]. Recently, we studied coherent transfer of optical orbital angular momentum in multi-order Raman sideband generation [19,20]. The energy of the ultrafast waveform produced in the scheme of References [17,18] is limited by the damage threshold of the pulse shaper.…”
Section: Introductionmentioning
confidence: 99%